Análisis causal de fallas y costos de operación y mantenimiento del sistema de distribución eléctrico de la Empresa Eléctrica Riobamba S.A. en la ciudad de Riobamba. - Guevara Uvidia, Fredy Alberto (2016)
In the study called causal analysis of faults and operating costs and maintenance on the electrical distribution system of Empresa Eléctrica Riobamba S.A. in the city of Riobamba, the objectives proposed are: to analyze by sector and type of condition by means of failure frequency analysis, so that later we can establish the operating costs and maintenance which are necessary in order to attend the failures found in the EDS in order to propose improvement actions for reducing the frequency of failures. In order to comply with the proposed objectives, they will be developed in several stages: Ishikawa diagrams to know the causes of failures for each substation in the city of Riobamba, frequencies per failure type were determined, after that the causes of failure were analyzed in order to determine the most frequent ones in each feeder belonging to the four substations in the city of Riobamba. After the analysis we got the most frequent failures and their percentages, as well as the failure causal frequency and their percentages. Starting from the times obtained, the next step is to calculate the operation and maintenance costs of every failure registered, after that, the prices of the material used for attending every one of the failures are determined. Then the operating and maintenance costs for every failure in several feeders belonging to the substations in Riobamba are determined. With the information gathered, an improvement plan for the most frequent failures is developed; it contains the general data, and the improvement actions to be taken for the possible reduction in the frequency of failures is proposed.